The role of somatic mosaicism in brain disease - Jourdon, Alexandre (Curr Opin Genet Dev, 2020)
In this review we discuss the importance of genetic somatic mosaicism and its impact on brain diseases. We start from introducing the different types of somatic mutations, their frequencies and abundances across development and lifespan. We then describe how weakness in DNA repair mechanisms influence their prevalence. Finally, we address their functional consequences in the brain and review recent research showing their unsuspected importance in several neurodevelopmental, psychiatric, and neurodegenerative diseases.